Design for manufacture of aircraft engine compressor blades - 231335 Venkatesh, V. C. (Vellore Chelvaraj); Shabudin Mat; Pang, Kwai Ching; International Conference on Advanced Manufacturing Technology (3rd : 2004 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2004)
19